RESTRAINING THE MOOD FOR LOVE: A SEMIOTIC ANALYSIS OF WONG KAR WAI’S IN THE MOOD FOR LOVE - Sutandio, Anton (Capture : Jurnal Seni Media Rekam, 2020)
This article attempts to explore the visual signs in Wong Kar Wai’s In the Mood for Love in the context of how they support and emphasize the topic of restraint through the film’s cinematography and misè-en-scèene. As the theoretical foundation, Peirce’s classification of signs into symbol, icon, and index is chosen in addition to Barthes’ five systems of meanings that are applied to cinema. The visual signs in focus are not limited to objects within the film, but also the characters’ actions as well as the cinematography. The findings show that certain signs are effectively displayed to signify and amplify the idea of restraint. Not only that, some signs evolve into different signs through intentional repetition to further emphasize the aforementioned idea and the arbitrary nature of the signs, and at the same time open the possibilities of different interpretations of the signs within the film.